Safety and early efficacy of irreversible electroporation for hepatic tumors in proximity to vital structures. Issue 5 (22nd October 2012) - Cannon, Robert; Ellis, Susan; Hayes, David; Narayanan, Govindarajan; Martin, Robert C.G.
Abstract Introduction Irreversible electroporation (IRE) has shown promise for ablation of lesions in proximity to vital structures in the preclinical setting. This study aims to evaluate the safety and efficacy of IRE for hepatic tumors in the clinical setting. Methods An IRB approved prospective registry of patients undergoing IRE for hepatic tumors over a 2‐year period. Factors analyzed included patient and tumor characteristics, treatment related complications, and local recurrence free survival (LRFS) for ablated lesions. LRFS was calculated according to Kaplan–Meier, with secondary analyses stratified by procedural approach (laparotomy, laparoscopy, and percutaneous) and tumor histology. Results There were 44 patients undergoing 48 total IRE procedures, 20 colorectal mets, 14 hepatocellular, and 10 other metastatsis. Initial success was achieved in 46 (100%) treatments. Five patients had 9 adverse events, with all complications resolving within 30 days. LRFS at 3, 6, and 12 months was 97.4%, 94.6%, and 59.5%. There was a trend toward higher recurrence rates for tumors over 4 cm (HR 3.236, 95% CI: 0.585–17.891; P = 0.178). Conclusions IRE appears to be a safe treatment for hepatic tumors in proximity to vital structures. Further prospective evaluation is needed to determine the optimal effectiveness of IRE in relation to size and technique for IRE of the liver. J. Surg. Oncol. 2013;107:544–549. © 2012 Wiley Periodicals, Inc.